2011
DOI: 10.1021/jp205950x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of β-Mo2C Facets from ab Initio Atomistic Thermodynamics

Abstract: The stability of β-Mo2C surfaces has been computed at the level of density functional theory under the consideration of the temperature, pressure, and molar ratios of CH4 /H2 and CO/CO2 gas mixtures by using ab initio atomistic thermodynamic calculations. It was found that the (001) surface is most stable at low temperature, whereas (101) becomes dominant at high temperature with CH4 as carbon source, and the computed surface stability is supported by the experimental X-ray diffraction pattern and intensity. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
99
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(121 citation statements)
references
References 71 publications
21
99
1
Order By: Relevance
“…26,27 Bulk optimizations carried out using the PBE functional yield lattice parameters (a = 3.04 Å, c = 4.73 Å) in agreement with previous values and those experimentally reported. 27 Note that surface slabs notation follows that of Wang and coworkers and are based on their bulk unit cell definition.…”
Section: Surface Models and Adsorption Studysupporting
confidence: 87%
“…26,27 Bulk optimizations carried out using the PBE functional yield lattice parameters (a = 3.04 Å, c = 4.73 Å) in agreement with previous values and those experimentally reported. 27 Note that surface slabs notation follows that of Wang and coworkers and are based on their bulk unit cell definition.…”
Section: Surface Models and Adsorption Studysupporting
confidence: 87%
“…al. [41] found that the Mo 2 C(001) surface is still present when more reactive carbon is present, although to a lesser extent. No previous studies have investigated the effects of hydrogen or oxygen on surface energies.…”
Section: Mo 2 C(001) Surfacementioning
confidence: 96%
“…No previous studies have investigated the effects of hydrogen or oxygen on surface energies. The Mo 2 C(001) surface is chosen as a starting point to investigate effects of hydrogen and oxygen on Mo 2 C surface stability since it has a simple structure, is the most close-packed surface, and is predicted to have significant presence on nanostructured Mo 2 C [40,41].…”
Section: Mo 2 C(001) Surfacementioning
confidence: 99%
See 2 more Smart Citations